The Era of the Martyrs : Remembering the Great Persecution in Late Antique Egypt - Hidding, Aaltje (2020)
In this book, Aaltje Hidding presents the first synthesis about how the Great Persecution (303–313 CE) was remembered in Late Antique Egypt. She unites research methods in memory studies with cognitive science and bases herself on archaeological, literary, papyrological and epigraphical sources in order to analyse how the Persecution was represented and remembered in three different cities along the Nile: Oxyrhynchus, Antinoopolis and Dendara.